Legal Aspects of Military and Defence Use of Outer Space - Malinowska, Katarzyna (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
This chapter examines the evolving landscape of military activities in outer space, considering the challenges it poses to existing space law. With an increasing number of nations utilising space for military and defence purposes, questions arise regarding the application of space law principles to these activities. This chapter delves into the notions of militarisation and weaponisation in outer space, exploring the role of space law in governing military applications and interpretation of the Space Treaties. The analysis extends to the evolution of international law, considering both binding and non-binding norms. Further, this chapter investigates the legal frameworks governing military use at the national and international levels, emphasising the need for regulations to address risks, including regarding space debris and sustainability concerns, as well as the prospective development of the European Union Space Law. Ultimately, the chapter aims to conceptualise the current and future integration of military aspects into the space regulatory framework and their interactions with contemporary challenges.Keywords: space militarisation, weaponisation, space law, space wars, sustainability, EU Space Law, space defence strategy.